Pilot Study of a Wearable Activity Monitor During Head and Neck Radiotherapy to Predict Clinical Outcomes. (25th March 2022) - Sher, David J.; Radpour, Sepeadeh; Shah, Jennifer L.; Pham, Nhat-Long; Jiang, Steve; Vo, Dat; Sumer, Baran D.; Day, Andrew T.
Abstract : PURPOSE: Given the established associations between performance status and survival in a variety of cancers, there is significant interest in using a biometric wearable device (WD) to predict outcomes in the oncology population. In this pilot study, we investigated the ability of a WD to predict meaningful clinical end points in patients undergoing head and neck radiotherapy. METHODS: Patients receiving head and neck definitive chemoradiotherapy or postoperative radiotherapy/chemoradiotherapy were enrolled in this pilot study, designed to show 90% compliance with using the device. Individuals were asked to wear the WD for 23 hours a day, and hospital admissions, pain medication usage, and FACT-G quality-of-life (QoL) score were prospectively recorded. RESULTS: Fifty-one patients were enrolled and started using the WD, but eight patients stopped wearing it, resulting in a compliance probability of only 84%. There were 15 hospital admissions, 13 of which were planned for feeding tube placement. There was no step count threshold that predicted the need for admission or more pain medications. However, among the 25 patients with a significant reduction in FACT-G score, the average reductions in daily steps during the week and weekend before the decline were 988 ( P = .005) and 1, 311 ( P = .018), respectively, and the odds of a QoL reduction were more than 4-fold higher among patients experiencing a week-to-week reduction of at least 1, 000 daily steps. There was no association between heart rate and any end point. CONCLUSION: Although not meeting the compliance goal, the majority of patients did use the WD. The WD signal could not identify patients requiring hospitalization or significantly more pain medication, but the finding of reduced step counts before a significant reduction in QoL is provocative. Abstract :